Challenges and Opportunities in the Livestock Industry for higher productivity and sustainability: The case of Albania - Risilia, Dori; Myslimi, Grisejda (European Scientific Journal, ESJ, 2024)
The livestock sector plays an important role in the economic development of the country. This sector is a source of income and employment for many Albanian families who live mainly in rural areas. A large part of the population in our country deals with livestock. But regardless of all the contributions that livestock makes to the food chain, financial sustainability, and the entire economy, this sector faces many challenges. Based on the literature review, a questionnaire to identify these challenges was constructed. The questionnaire contains questions with answers on the Likert scale, is addressed to livestock farmers in Albania, and serves to identify the main challenges affecting the livestock sector. The questionnaire divided the challenges of the livestock sector into five parts, including animal welfare and livestock production, sustainable practices and environmental sustainability, market challenges, information, communication technologies and livestock marketing challenges, and challenges of innovations in livestock production. Animal welfare affects the productivity of the livestock sector. The risk of the spread of epidemic diseases and the high costs of vaccination and medications are a concern for Albanian farmers, who often have difficulties ensuring sustainable profits. In recent years, the livestock sector has faced high input costs. Lack of infrastructure also hinders the efficiency of the livestock sector. The need for sustainable practices and environmental sustainability demands more attention. While farmers want to adopt sustainable livestock methods, they face difficulties in implementing them. Unpredictable livestock prices complicate financial planning for farmers. In addition, small farms face challenges competing with larger ones. Farmers face difficulties in becoming part of new markets due to a lack of effective marketing channels. The lack of a labor force is the biggest challenge that the livestock sector in Albania is facing. Innovation often serves to solve many problems in the livestock sector. Farmers use new technologies to increase livestock productivity. But the use of new technologies requires knowledge, which Albanian farmers often don’t have. They do not have the proper education to understand and apply these technologies. In conclusion, this paper aims to highlight the various problems faced by the livestock sector. Overcoming these problems by dealing directly with them can increase the productivity of the livestock sector, ensuring a better future for the industry.